Analisis Pengaruh Penyaluran Zakat oleh BAZNAS Terhadap Jumlah Mustahik Miskin di Provinsi Jambi Periode 2000-2014 - Rahmat Hidayat; Adi Bhakti; Ridwan Ridwan (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2017)
This study entitled Analysis of the Influence of Zakat Distribution by BAZNAS to The Poor Mustahik In Jambi Province Period 2000-2014. Interest of this study was to 1). To know and analyze the development and distribution of zakat in BAZNAS to mustahik number of poor in Jambi province during the years 2000-2014; 2).Analyze the effect of the distribution of zakat by BAZNAS to the number of poor mustahik in Jambi Province during the years 2000-2014. This research uses descriptive and quantitative analysis methods. Quantitave descriptive analysis method is used to analyze the effect of the distribution of zakat by BAZNAS the number of poor mustahik in Jambi Province during the years 2000-2014. Based on the results of the analysis showed average productive distribution of zakat to the poor mustahik in Jambi province during the years 2000-2014 amounted to Rp 300.725.733, an increase of 33,48 percent annually and the number of poor mustahik in Jambi province during the years 2000-2014 are a number 1,181 inhabitants or an increase of 19,12 percent annually. As well, distribution productive zakat BAZNAS Jambi province turns a significant effect on the number of poor mustahik during the period 2000-2014.